Using latent profile and transition analyses to understand patterns of informant ratings of child depressive symptoms. (August 2018) - Herman, Keith C.; Cohen, Daniel; Reinke, Wendy M.; Ostrander, Rick; Burrell, Lori; McFarlane, Elizabeth; Duggan, Anne K.
Abstract: The present study examined the latent profiles of child, parent, and teacher ratings of child depressive symptoms in a developmental sample of children from Hawaii at two time points (2nd and 3rd grade). The study attempted to identify patterns of agreement and discrepancy among raters and correlates of these patterns to test a new theory for understanding rating disagreements as Divergent Operations. Three profiles best described the ratings at both time points: Child-Only High Depression, Child-Only Mild Depression, and Normative (non-depressed). Second and third grade measures of child social skills, externalizing symptoms, attention problems, and language and academic competence confirmed the distinctiveness of these classes which provides support for a Divergent Operations perspective. Latent transition analyses suggested that depressive symptoms were relatively transient for each class. Implications regarding the measurement and identification of child depressive symptoms across development and the meaning and use of discrepant ratings are discussed.